Pengaruh Aroma Terapi Lavender Dan Musik Bahasa Inggris Untuk Meningkatkan Kualitas Tidur Lansia Di Yayasan Roasro Medan - Zulkarnain Batubara; Vitalia Hanako; Rosmega Rosmega; Yesi Winata Hutagalung (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Insomnia is one of the most common sleep problems in the elderly due to aging. These sleep problems have an impact on reducing the quality of sleep in the elderly. Lavender aromatherapy and English music are one way to increase sleep needs. This study aims to analyze the effect of a combination of lavender aroma therapy and English music on the sleep quality of elderly people with insomnia. The design of this research is quasi-experimental with a pre-test and post-test control group approach. The population is elderly people with sleep disorders at the Roasro Simalingkar B Medan Foundation. The total sample was 32 elderly people with insomnia who were divided into two groups using random sampling who met the inclusion criteria. The independent variables of this research are lavender aromatherapy and English music, while the dependent variable is the sleep quality of elderly people with insomnia. Data were collected using a structured questionnaire and analyzed using the Wilcoxon Signed Rank Test and Mann Whitney Test with a significance level of 0.05. The results showed that there was an effect of the combination of lavender aromatherapy and English music on sleep quality (p=0.000) in the treatment group. Meanwhile, in the control group there was no effect on sleep quality results (p=0.564). The comparison results stated that there was a difference in the post test sleep quality (p=0.000). The combination of lavender aromatherapy and English music has a significant effect on the sleep quality of elderly people with insomnia.